The relationship between moral sensitivity, ethical climate, and job strain with patient privacy from viewpoint of operating room staffs - Elaheh Sepehrirad (Iranian Journal of Nursing and Midwifery Research, 2021)
Background: The privacy of patients in the operating room is in particular importance. The results of previous studies have shown that various factors are affecting in this context. The aim of this study is to evaluate the relationship between moral sensitivity, ethical climate, and job strain with respect to patients' privacy in operating rooms. Materials and Methods: All of operating rooms nurses of teaching hospitals affiliated to Ardabil University of Medical Sciences were entered into this descriptive-analytical study with census sampling method in 2019. To collect data, standard surveys of moral sensitivity, ethical climate, job strain, and privacy were used. Data were analyzed by SPSS15 software using descriptive and analytical statistics methods (independent t-test, ANOVA, Pearson correlation, and regression analysis). Results: There was a positive significant relationship between moral sensitivity and privacy (r = 0.56, p < 0.001) and ethical climate and privacy (r = 0.60, p < 0.001), too. But, there was an inverse and significant correlation between job strain and privacy (r = -0.69, p < 0.001). The results also showed that moral sensitivity is the best predictor of patients' privacy. Conclusions: Despite the predictability of all variables, results showed that moral sensitivity is the most important component in patients' privacy. In this regard, by increasing the moral sensitivity of nurses, the privacy of patients can be improved.